Tourism and preventive measures taken in transmission of COVID-19 in Galle District, Sri Lanka - Kanaththa Hewage Priyantha Jeewarathne; Wenura Kumara Singarachchi; Bhadra Chandanie Mallawaarachchi; Don Chinthaka Athukorala; Kanchitha Thathsara Samararathna; Nalin Prasanna Wijesekara; Dinesh Gunarathne; Indeewarie Eranga Gunaratna (College of Community Physicians of Sri Lanka, 2020)
No abstract available